AAZTA-Derived Chelators for the Design of Innovative Radiopharmaceuticals with Theranostic Applications - Cyril Fersing; Nicolas Masurier; Léa Rubira; Emmanuel Deshayes; Vincent Lisowski (MDPI AG, 2022)
With the development of 68Ga and 177Lu radiochemistry, theranostic approaches in modern nuclear medicine enabling patient-centered personalized medicine applications have been growing in the last decade. In conjunction with the search for new relevant molecular targets, the design of innovative chelating agents to easily form stable complexes with various radiometals for theranostic applications has gained evident momentum. Initially conceived for magnetic resonance imaging applications, the chelating agent AAZTA features a mesocyclic seven-membered diazepane ring, conferring some of the properties of both acyclic and macrocyclic chelating agents. Described in the early 2000s, AAZTA and its derivatives exhibited interesting properties once complexed with metals and radiometals, combining a fast kinetic of formation with a slow kinetic of dissociation. Importantly, the extremely short coordination reaction times allowed by AAZTA derivatives were particularly suitable for short half-life radioelements (i.e., 68Ga). In view of these particular characteristics, the scope of this review is to provide a survey on the design, synthesis, and applications in the nuclear medicine/radiopharmacy field of AAZTA-derived chelators.